PLACEMENT TEST INFORMATION SYSTEMS STUDENT ASSESSMENT INSTITUTIONS IN ENGLISH COURSE IECPASAR REBO - Dwi Anggarinaratih Ratnasari; Irfan, SKom, MMSI Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2000)
The problems faced in these institutions lies in the assessment system for the placement test students who are still done manually, which is a lot of manual system faced various obstacles and inefficiencies both in terms of time and of the workings of the organizer committee test. For that formed the design of the system to replace existing systems with computerized systems. So that the results obtained from the new system isexpected to assist the performance of these institutions. It is expected that by using a computer system can be run more effectively and efficiently than the manual method.